2019
DOI: 10.1002/ajmg.a.61067
|View full text |Cite
|
Sign up to set email alerts
|

Congenital clubfoot in Europe: A population‐based study

Abstract: We aimed to assess prevalence, birth outcome, associated anomalies and prenatal diagnosis of congenital clubfoot in Europe using data from the EUROCAT network, and to validate the recording of congenital clubfoot as a major congenital anomaly by EUROCAT registries. Cases of congenital clubfoot were included from 18 EUROCAT registries covering more than 4.8 million births in 1995-2011. Cases without chromosomal anomalies born during 2005-2009, were randomly selected for validation using a questionnaire on diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 30 publications
6
49
2
Order By: Relevance
“…As a common developmental malformation of newborns, clubfoot affects approximately 2% of newborns (Wang et al, 2019). If not actively and timely treated, this deformity will accompany the child for a lifetime, which will not only affect the appearance of the child, including walking difficulties or even a disability, but also cause serious adverse effects on the mental health of the child.…”
Section: Introductionmentioning
confidence: 99%
“…As a common developmental malformation of newborns, clubfoot affects approximately 2% of newborns (Wang et al, 2019). If not actively and timely treated, this deformity will accompany the child for a lifetime, which will not only affect the appearance of the child, including walking difficulties or even a disability, but also cause serious adverse effects on the mental health of the child.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital talipes equinovarus, also named clubfoot, is one of the most common major congenital distal skeletal abnormalities in newborn infants with a prevalence of 1.13 per 1000 livebirths [ 1 ]. A previous study confirmed that about 20% of clubfoot patients are connected with chromosomal abnormalities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence for a genetic basis for clubfoot is the differences in clubfoot prevalence across ethnic populations, with the lowest prevalence in Chinese (0.39 cases per 1000 live births) and highest in the Hawaiians and Maoris (7 per 1000) [10,11]. The neuromuscular etiological concepts in congenital clubfeet yield important information regarding recurrent deformities, especially dynamic supination [12,13,14].…”
Section: Introductionmentioning
confidence: 99%